Bioactive triterpenoids from Sambucus javanica Blume. Issue 19 (1st October 2020) - Chen, Feilong; Liu, Dong-Li; Wang, Wei; Lv, Xiao-Man; Li, Weixi; Shao, Li-Dong; Wang, Wen-Jing
Abstract: A new triterpene, javablumine A (1 ) along with six known ones were isolated from the aerial parts of Sambucus javanica Blume. They were identified as 3β, 23-dihydroxy-11α, 12α-epoxy-urs-20(30)-en-28, 13β-olide (1 ), ursolic acid (2 ), pomolic acid (3 ), oleanic acid (4 ), 2α-hydroxy-oleanolic acid (5 ), α-amyrin (6 ), and lupeol palmitate (7 ), respectively. Compounds 1 and 3 exhibited inhibitory effect against nitric oxide (NO) production in lipopolysaccharide (LPS)-activated RAW264.7 macrophage cell lines with IC50 values of 17.4 and 26.2 μM, respectively. Graphical Abstract: